Marketing, Processing and Utilization Community of Practice. Rebranding OFSP for Health and Wealth: Proceedings of CoP meeting held in Kunduchi Beach Hotel, Dar es Salaam 14-16 March 2016. - International Potato Center (2016)
The Marketing, Processing and Utilization Community of Practice (CoP) met on 14 and 16 March 2016 in Kunduchi Beach Hotel, Dar es Salaam. The CoP brings together professionals working on all levels of the sweetpotato value chain, as well as private sector players who are innovating processing and utilization of orange-fleshed sweetpotato for commercial products. This CoP meeting was held under the umbrella of the Africa-wide Sweetpotato for Profit and Health Initiative (SPHI). SPHI is a 10-year initiative led by the International Potato Centre (CIP), and it is expected to improve the lives of 10 million households by 2020 in 17 target countries. Launched in 2009, the project had already reached over 1 million households by the end of December 2014. One of the key intervention areas is improving the sweetpotato value chain by researching and implementing actions that will remove bottlenecks related to processing, marketing and utilization of sweetpotato products. The overall objective continues to be to develop the essential capacities, products, and methods to reposition sweetpotato in food economies to alleviate poverty and undernutrition in Africa. The meeting was officially opened by Madjaliwa Nzamwita. In his opening address, he praised the remarkable progress made by scientists working on potato and urged participants to take up the challenge to achieve faster progress in sweetpotato. He urged the participants to assist farmers get clean planting material and to work hand in hand with food processing companies by showing them prototypes of sweetpotato products they can make to increase both their earnings and the demand for fresh sweetpotato roots. He stressed the importance of working with health centres in organising trainings on fighting malnutrition among their communities. He explained that a cooking demonstration had been organised for the cooks to help increase demand for sweetpotato by demonstrating the diverse range of sweetpotato products that they could produce and asked them to replicate this approach in their countries. He stated that as a community of practice, it was possible to amplify the impact of individuals working across the continent, and highlighted what the CoP could do to contribute to the achievement of the SPHI goal. He urged the members to take one step further to make sure that by 2020, lives of 10 million households get better and to record the annual progress.